1954
DOI: 10.1017/s0021859600045731
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the breeding records of a herd of pigs

Abstract: 1. A survey and. statistical analysis of the records of litters born in the N.I.R.D. herd of Large White pigs over a period of 16 years are presented.2. The mean length of gestation was 114 days for both gilts and sows.3. The mean numbers of pigs born alive and born dead per litter from gilts, 10·0 and 0·2 respectively, were both significantly smaller than the corresponding figures for sows, 11·8 and O·8. No seasonal differences were found.4. The mean total losses of pigs from birth to weaning at 8 weeks were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

1958
1958
1982
1982

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
1
7
1
Order By: Relevance
“…Berliner (1942) noted seasonal variation in the reproductive performance of mares and jennets in Mississippi. Braude et al (1954) found no seasonal influence on the fertility of swine.…”
Section: Seasonal Changes In Semen Quality and Fertilitymentioning
confidence: 80%
See 2 more Smart Citations
“…Berliner (1942) noted seasonal variation in the reproductive performance of mares and jennets in Mississippi. Braude et al (1954) found no seasonal influence on the fertility of swine.…”
Section: Seasonal Changes In Semen Quality and Fertilitymentioning
confidence: 80%
“…The relation was similar for jennets except that they had longer gestations. Braude (1954) reported no seasonal effects on the number of pigs farrowed when the two seasons--November to April and May to October == were considered. As the gilts were slaughtered, Wiggins~ al, (1950) observed the reproductive organs of gilts farrowed in different seasons,…”
Section: Seasonal Effect On Reproductive Performance 10mentioning
confidence: 98%
See 1 more Smart Citation
“…This was another expression of the earlier mentioned difference between effect of parity on litter weights and average pig weights when eliminating versus ignoring litter size. Many authors have found the lowest weights in the first parity (Lush & Molln, 1942;Korkman, 1947;Braude et al, 1954;Lynch, 1965;Eikje, 1970;Hetzer & Miller, 1972), but for higher parties the picture was more complex. Lush & Molln (1942) found the highest litter weights at weaning for 2 year old sows both in their own study and in the five studies they reported.…”
Section: Aceruge Pig Weightmentioning
confidence: 99%
“…This was in agreement with Lynch (1965) who found the highest 21-day weights for parities 2 and 3, and Eikje (1970) who found the highest values for the third parity, both for litter weights and average pig weights at 21 days. Korkrnan (1947) found litter size to be decisive for the best parity between the second and sixth, while Braude et al (1954) did not find any effect of later parities on average weaning weight. Both Omtvedt et al (1965) and Hetzer & Miller (1972) found an effect of age of the gilts on average birth weights.…”
Section: Aceruge Pig Weightmentioning
confidence: 99%